1982
DOI: 10.1002/hlca.19820650510
|View full text |Cite
|
Sign up to set email alerts
|

Persistance of the Cyclopnane Radical Anions and its Relation to Structure

Abstract: SummaryReactions of [2,]cyclophanes (N = 2,. . .6) with solvated electrons in 1,2-dimethoxyethane at 193 K have been studied by ESR. and ENDOR. spectroscopy. All but the two most highly bridged cyclophanes ( N = 5 and 6) are reduced to paramagnetic species under these conditions. Whereas the radical anions of [2.2]-paracyclophane and p3] (1,2,4)-and p4] (1,2,4,5)cyclophanes are sufficiently persistent to be characterized by their hyperfine data, those of the remaining five cyclophanes undergo a rapid cyclizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…While the oxidation of unsubtituted [2.2]paracyclophane to the corresponding radical cation is irreversible in solution, 12 the radical anion of [2.2]paracyclophane is more persistent. [13][14][15][16] Badger and Brocklehurst reported absorption spectra of both the radical anion and the radical cation of [2.2]paracyclophane which were generated by γ-radiolysis of glassy solutions at low temperatures. 17 The absorption spectrum of the radical cation was compared with the photoelectron spectrum of neutral [2.2]paracylophane by Heilbronner et al 18 By ESR and ENDOR spectroscopy it was shown that a substitution of [2.2]paracyclophane by electron donating groups such as methyl or methoxy substituents leads to a stabilization of the corresponding radical cations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the oxidation of unsubtituted [2.2]paracyclophane to the corresponding radical cation is irreversible in solution, 12 the radical anion of [2.2]paracyclophane is more persistent. [13][14][15][16] Badger and Brocklehurst reported absorption spectra of both the radical anion and the radical cation of [2.2]paracyclophane which were generated by γ-radiolysis of glassy solutions at low temperatures. 17 The absorption spectrum of the radical cation was compared with the photoelectron spectrum of neutral [2.2]paracylophane by Heilbronner et al 18 By ESR and ENDOR spectroscopy it was shown that a substitution of [2.2]paracyclophane by electron donating groups such as methyl or methoxy substituents leads to a stabilization of the corresponding radical cations.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the investigation of charged cyclophane systems is of great interest for studying charge-transfer processes over the [2.2]paracyclophane moiety. While the oxidation of unsubtituted [2.2]paracyclophane to the corresponding radical cation is irreversible in solution, the radical anion of [2.2]paracyclophane is more persistent. Badger and Brocklehurst reported absorption spectra of both the radical anion and the radical cation of [2.2]paracyclophane which were generated by γ-radiolysis of glassy solutions at low temperatures . The absorption spectrum of the radical cation was compared with the photoelectron spectrum of neutral [2.2]paracylophane by Heilbronner et al By ESR and ENDOR spectroscopy it was shown that a substitution of [2.2]paracyclophane by electron donating groups such as methyl or methoxy substituents leads to a stabilization of the corresponding radical cations. , By these methods, a strong intramolecular electronic coupling between the two aromatic subunits was found which is in agreement with the interpretation of the absorption signal of the [2.2]paracyclophane radical cation as a charge resonance band by Badger and Brocklehurst .…”
Section: Introductionmentioning
confidence: 99%